Problems of private investment in agriculture of the Republic of Kazakhstan ("Journal "U". Economy. Management. Finance.", 2022)
In the current conditions of the complication of the global economic and food situation, significant investments in agriculture are needed to accelerate the increase in food production. Private investment can play a vital role in ensuring inclusive economic growth, environmental sustainability and reducing the threat of a food crisis. To do this, it is necessary to create affordable mechanisms for attracting private investment in the industry, such as direct investment funds. In addition, private investment should be properly regulated and follow some key principles such as focusing on local food markets, working with producer and supplier organizations, protecting the rights of small producers, individual entrepreneurs. The main purpose of the study is to find and justify tools for attracting private investment in the industry. The methodology is based on the analysis of data from the agro-industrial complex of the country and comparison of some data with developing countries.
Keywords: Investments; agriculture; agribusiness; public investment; private investment; direct investment funds; commodity structure of exports and imports; domestic food market